Information retrieval in digital watermarking. - Hernandez Martin, J.R.
Digital watermarking, the art of robust information hiding in images, has gained a large interest in both research and industry in the past few years. Every watermarking system has two main parts: watermark embedding and watermark extraction/detection. Previous developments in the theoretical analysis of digital watermarking schemes have shown that there is a direct link between digital watermarking and communication theory. These parallels are extremely helpful when it comes to designing efficient and optimal watermark detectors. We focus on this issue and investigate how to design good watermark detectors taking into account the basics of communication theory. Furthermore, we discuss different ways to achieve robustness to geometrical attacks and elaborate on watermark attacks
Keywords: Communication theory; Digital watermarking; Efficient watermark detector; Geometrical attacks; Image coding; Industry; Information retrieval; Optimal watermark detector; Research; Robust information hiding; Spread spectrum watermarking; Watermark attacks; Watermark embedding; Watermark extraction/detection.; Watermarking system